Confidence Crisis in the Application of Cloud Computing in the Industrial Companies in Jordan a Field Study - Al-Zoubi, Abdullah Mohammed; Al-Masaiid, Ibtissam (Journal of Accounting, Business and Management (JABM), 2019)
The current study aimed at determining the extent to which the industrial companies in Jordan have a confidence crisis in applying cloud computing. This crisis is divided into three different categories: a confidence crisis in programs and operations, a confidence crisis in service providers and a confidence crisis in the security and protection offered by service providers. In order to achieve the purpose of the research, a questionnaire was designed covering the three areas of confidence crisis. (120) questionnaires were distributed on a stratified random sample of (81) industrial companies in Al Hassan industrial estate in Irbid; (104) valid questionnaires were retrieved. The results of the study show that there is indeed a confidence crisis in the application of cloud computing in the Jordanian industrial companies within the three aforementioned domains. The researchers recommend that the service providers should educate on the cloud computing mechanisms and how the systems, applications and stored data are protected, so as to avoid such a confidence crisis in the industrial companies.